2015
DOI: 10.1016/j.hrthm.2015.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous nerve activity is more accurate than heart rate variability in estimating cardiac sympathetic tone in ambulatory dogs with myocardial infarction

Abstract: Background We recently reported that subcutaneous nerve activity (SCNA) can be used to estimate sympathetic tone. Objectives To test the hypothesis that left thoracic SCNA is more accurate than heart rate variability (HRV) in estimating cardiac sympathetic tone in ambulatory dogs with myocardial infarction (MI). Methods We used an implanted radiotransmitter to study left stellate ganglion nerve activity (SGNA), vagal nerve activity (VNA), and thoracic SCNA in 9 dogs at baseline and up to 8 weeks after MI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…810 In addition, SCNA is more effective than heart rate variability in estimating the sympathetic tone. 11 Encouraged by these results, we 12 showed that it is possible to simultaneously record electrocardiogram (ECG) and SKNA using conventional ECG electrodes in humans. The same electrical signal can be filtered between 0.5 Hz and 150 Hz to display ECG, while high pass filtered at 200 Hz or higher to display SKNA.…”
Section: Introductionmentioning
confidence: 95%
“…810 In addition, SCNA is more effective than heart rate variability in estimating the sympathetic tone. 11 Encouraged by these results, we 12 showed that it is possible to simultaneously record electrocardiogram (ECG) and SKNA using conventional ECG electrodes in humans. The same electrical signal can be filtered between 0.5 Hz and 150 Hz to display ECG, while high pass filtered at 200 Hz or higher to display SKNA.…”
Section: Introductionmentioning
confidence: 95%
“…None of the above comparisons were statistically significant. These findings might be partially explained by our previous study 11 which showed that HRV parameters poorly correlates with SGNA in ambulatory dogs.…”
Section: Resultsmentioning
confidence: 84%
“…Extra-cardiac sympathetic neurons are located across numerous thoracic ganglia in particular in the stellate, middle cervical, superior cervical and mediastinal ganglia (Janes et al, 1986;Ardell and Armour, 2016). The electrophysiological properties of neurons located within the stellate ganglion and postganglionic axons traveling along the cardiac sympathetic nerve (CSN) have been studied extensively in several animal models in vivo, including ambulatory cats (Tsuchimochi et al, 2002), dogs (Han et al, 2012;Chan et al, 2015) sheep (Jardine et al, 2002(Jardine et al, , 2005(Jardine et al, , 2007Charles et al, 2018) and anesthetized cats (Nishikawa et al, 1994). Experiments conducted in conscious and anesthetized cats with either intact or denervated baroreceptors have been the model of choice to study periodic oscillations in CSNA.…”
Section: Lf Oscillations In Cardiac Sympathetic Postganglionic Fibersmentioning
confidence: 99%